The Effect of Aiding Apparatus and Tools on Pressure Variable in Individuals with Flatfoot aged 10 – 12 Years Old - Muhammed, Majed al deen; Sabaa, Ahmed (Journal of Physical Education, 2019)
The research aimed at designing and manufacturing mechanical apparatus and tools that help treat flatfoot as well as identifying the effect of treatment exercises using the apparatus and tools in pre and posttests for both feet. The researcher used the experimental method on (8) pupils from Al Samaraa district schools. After pretests and treatment program application for (6) weeks with (6) sessions per week, the data was collected and treated using proper statistical operations to conclude the following: Measuring foot print (Clarks) is not a standardized means for measurement because it does not give an accurate result of flat foot in subject's understudy. Clarks can be used for first diagnoses and discovering individuals with flat foot, Using X – ray is a more accurate means for measuring flat foot, using aiding apparatus, tools and the treatment exercises have a positive effect on speeding treatment.